Eksistensi Pendidikan Lingkungan Hidup dalam Ranah Pendidikan Islam - Irham Fajriansyah; Uswatun Hasanah; Ali Murtadho (Qiro'ah : Jurnal Pendidikan Agama Islam, 2021)
The current environmental issues are part of a global crisis that often becomes a concern of discussion in the world stage. Various approaches have been taken to resolve the crisis, but the results are still debatable. One of the most ideal approaches is to use an Islamic education approach. This research aims to examine the existence of environmental education in Islamic education. This research is a literature research with documentation methods and use content analysis for its analytical techniques. The results of research shows that Islamic education can be used as a means to realize the values of environmental education, because there is a close relationship between environmental education and Islamic education, such as from the material, methods and goals aspects that ultimately achieve the goal of forming awareness of each individual to the environment issues.